Coastal Sceneries of Albania, An Emerging 3S Destination: Analysis of Physical Characteristics and Human Activity Impacts - Alfredo Fernández Enríquez; Alexis Mooser; Giorgio Anfuso; Javier García-Onetti (Land)
The increase in tourism economic benefits is the most common purpose along the Mediterranean coastal regions but, very often, conflicts of interest arise between short-term benefits and long-term conservation goals. This is particularly the case of Albania, a very popular emerging “Sun, Sea and Sand” (3S) destination characterized by massive fluxes of national/international visitors during the summer period. Among beach users’ preferences, global studies show that five parameters of greater importance stand out from the rest, i.e., safety, facilities, water quality, no litter, and scenery, and the latter is the main concern of this study. Albania is well known for its outstanding natural coastal beauty which was assessed at 40 sites by using the Coastal Scenic Evaluation System (CSES) method. Based on the evaluation of 26 physical/human parameters and using weighting matrix parameters and fuzzy logic mathematics, the technique enables one to obtain an Evaluation Index (D) that allows one to classify each investigated site into five scenic classes, from Class I (extremely attractive natural sites; D ≥ 0.85) to Class V (very unattractive developed urban/industrial sites; D < 0.00). Pragmatically, the higher the “D” value is, the better the site scenery is. After a long process of field testing along the whole Albanian coastline (ca. 523 km in length), selected sites were chosen in rural/remote environments (22), villages (6), and urban (4) and resort areas (8) to reflect the Albanian coastal typicity and characterize the scenic impact of human activities. Most sites belonged to Class III (14), Class IV (13), Class II (8), and Class I (1). Several sites could be upgraded to Class I or Class II with slight management efforts, e.g., by carrying out cleaning operations or by reducing intrusive beach facilities.